The accuracy of fish otolith analysis and some validation methods - Do, Hoang Huu (Vietnam Journal of Marine Science and Technology, 2014)
Age structure and growth of fish is an extremely important in fishries management. The data help policy makers has good strategies to manage and catch fish more effectively and sustainable. Although there are many studies on fish age determination relying on otolith, the methods are still essential to be validated for each species, each method and studied area, hence fish otolith formation is affected by many endogenous and exogenous factors. This paper shows the fish otolith function and its formation and introduces some validation methods, including: rearing fish, mark and release, radiometric assessment, assays of bomb radiocarbon, counting daily increments between annuli, length-frequency modes and validating the first growth increment.